2000
DOI: 10.1021/ie990111a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Reaction between Ozone and p-Hydroxybenzoic Acid in a Semibatch Reactor

Abstract: The kinetic regime in the ozone and p-hydroxybenzoic acid reaction system at pH 3 and 7 can be considered a slow reaction, whereas at pH 10 the rapid reaction mainly occurred in the liquid film and developed in the fast absorption kinetic regime. On the basis of the discussion of kinetic regime and the experimental observations, the kinetic expressions for the p-hydroxybenzoic acid, glyoxal, and dissolved ozone concentration can be developed for both pH 3 and 7 and were verified with the experimental data. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Some researchers (Lykins et al, 1994;Chang et al, 2002) revealed that preozonation reduced the DBP formation potential (DBPFP) of NOM due to the decrease of the strength of aromatic C@C structure within NOM after ozonation. However, other researchers reported the enhancement of DBPFP during ozonation due to the different oxidation conditions (Reckhow et al, 1986;Ko et al, 2000).…”
Section: Introductionmentioning
confidence: 92%
“…Some researchers (Lykins et al, 1994;Chang et al, 2002) revealed that preozonation reduced the DBP formation potential (DBPFP) of NOM due to the decrease of the strength of aromatic C@C structure within NOM after ozonation. However, other researchers reported the enhancement of DBPFP during ozonation due to the different oxidation conditions (Reckhow et al, 1986;Ko et al, 2000).…”
Section: Introductionmentioning
confidence: 92%
“…In this work, p ‐hydroxybenzoic acid, a phenolic model compound found in wastewater from food processing factories, has been oxidized in aqueous solutions by means of UV radiation and by the combination of ozone and UV radiation. Previously, this compound has been studied using ozone17–20 and Fenton's reagent 21. Some intermediates formed were identified by HPLC and GC/MS.…”
Section: Introductionmentioning
confidence: 99%
“…Some intermediates formed were identified by HPLC and GC/MS. Among them aldehydes,18, 19 such as glyoxal, methanal, methyl glyoxal and ethanal, carboxylic acids,21 such as maleic and oxalic acids, catechol and hydroquinone21 were analysed throughout the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Ozone process has been utilized in thousands of water treatment applications such as municipal water (or wastewater) treatment plants, cooling towers, ultrapure water, marine aquaria, beverage industries, industrial process water, swimming pools, bottled-water plants, aquaculture, and food processing. It can oxidize the micro-pollutants and reduce the amount of disinfection by-product (DBP) precursors formed in drinking water [1], such as organic peroxides, aliphatic aldehydes, hydrogen peroxides, mixed functional and saturated carbox-ylic acids, etc. Some of the DBPs such as aldehydes and/or chlorinated aldehydes would be potential health hazards, leading to the increase of bacterial populations in distribution systems.…”
mentioning
confidence: 99%
“…Some of the DBPs such as aldehydes and/or chlorinated aldehydes would be potential health hazards, leading to the increase of bacterial populations in distribution systems. Three oxygen molecules will combine together to form ozone, as shown in Equation (1); this is an endothermic reaction:…”
mentioning
confidence: 99%